Overview of Vehicle Tranportation Implementation In KMP.Siginjai On The Jepara - Karimunjawa Track - Kodrat Alam; Broto Priyono; Besar Alviansyah (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2021)
The Jepara Ferry Port is managed and operated by the Jepara Regency Transportation Service, under the supervision of the Land Transportation Management Center for Region X Central Java Province and D.I. Yogyakarta. Meanwhile, the operation of the ferry is carried out by PT. ASDP Indonesia Ferry (Persero) Jepara branch. This ferry port only serves 1 (one) pioneer crossing, which is served by 2 (two) ferry boats. This ferry port plays an important role in connecting Java Island with Karimunjawa Island. Because this port is the closest crossing access to the Karimunjawa Islands. This ferry port is served by 1 (one) Ro-Ro type ship and 1 (one) fast boat type owned by 2 (two) shipping companies, namely PT. ASDP Indonesia Ferry (Persero) and PT. Sakti Inti Makmur cruise. Based on the results of the survey that has been carried out, the vehicle handling system on the KMP Ro-Ro ship. Siginjai is not in accordance with the Regulation of the Minister of Transportation Number 115 of 2016 concerning Procedures for Transporting Vehicles on Ships. The distance from one vehicle to another is too close which will result in damage to the vehicle body. There are also several vehicles transported at KMP. Siginjai does not use lashing so it is very dangerous for vehicle operators or ship operators and can also affect the stability of the ship if the vehicles move during the trip.